PELAKSANAAN PEMBAGIAN WARISAN PADA MASYARAKAT ADAT NIAS (STUDI PADA MASYARAKAT ADAT NIAS DI KABUPATEN NIAS SELATAN) - MEMORI PERDAMAIAN LAOLI (PREMISE LAW JURNAL, 2017)
Adat (customary) inheritance law is the whole legal provesions and adat guidance which regulates the ttansfer and bequeathing inheritance with all its consequences during the testator is still alive or dead. Inheritance is related to the process of bequeathing and transferring concrete and non-concrete property from one generation to another one, so thatit is closely related to the problem of in heritance. Today, dissatisfaction in heritance distribution can be seen in the community of Nias in Which conflict of interest among to parties can cause disputes among heirs in distributing inheritance. The disputes can be followed u to court or it is not impossible when someone kills his own brother because he thinks that the inheritance is not equally distributed, starting from long arguments in which each party claims that he has the right for the land since the testator has died. Keywords: Inheritance, Adat, Nias